PENGARUH AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN KEUANGAN DAERAH TERHADAP KINERJA INSTANSI INSPEKTORAT ACEH - Zulkifli Umar; Cut Fittika Syawalina; Khairunnisa Khairunnisa (KOLEGIAL, 2018)
This research was conducted to determine the effect of accountability and transparency on the performance of the Aceh Inspectorate agencies. The object of this research is transparency, accountability and agency performance. The number of samples in this study were 42 respondents. Data collected using questionnaires with units of Likert scale units. The analytical equipment used in analyzing the data is multiple linear regression. Simultaneous results show that accountability and transparency jointly influence the performance of the Aceh Inspectorate Office, accountability partially influences the performance of the Aceh Inspectorate Office agencies with a regression coefficient of 0.155 and transparency has a partial effect on the performance of agency auditors in the Aceh Inspectorate Office with a regression coefficient of 0.137. The results of this study imply that the accountability and transparency possessed by auditors will have a real influence in improving agency performance for auditors of the Aceh Inspectorate Office.